GEOMORPHOLOGICAL EVOLUTION OF THE BASIN OF ATHENS - ΠΑΥΛΟΠΟΥΛΟΣ, Κ.; ΚΟΤΑΜΠΑΣΗ, Χ.; ΣΚΕΝΤΟΣ, Α. (Bulletin of the Geological Society of Greece, 2005)
This study is based on the collection, process and management of the geographical, geological and geomorphological data of the area of the basin of Athens with main objects the construction of a geomorphological map of the study area, the description and the study of the geoshapes that exist and the approach of the geomorphological evolution of the basin. The main erosion forms such as gorges and erosion surfaces are observed in the northern part of the study area at the mountain of Parnitha compare to the deposition forms that we meet in the southern part. As well as landforms like inselberg and alluvial fans give important information for the geomorphological evolution of the basin of Athens.